Ang Katwiran ng mga Hibik - ZAFRA, GALILEO S. (Philippine Humanities Review, 2021)
The poems “Hibik ng Pilipinas sa Inang Espanya” by Hermenegildo Flores, “Sagot ng Espanya sa Hibik ng Pilipinas” by Marcelo H. del Pilar, and “Katapusang Hibik ng Pilipinas” by Andres Bonifacio form part of the triumvirate poems that served as propaganda materials during the Propaganda period (1880-1895) and the Philippine Revolution (1896-1898) against the church, and later, against Spain. This paper locates these poems in the tradition of Philippine poetic jousts and folk drama, particularly the duplo, a traditional dramatic form or folk game performed as part of the Tagalog customs for the departed. The study will highlight the aspects of the hibik (plea) poems as argumentative poems, and as such, will present another reading of the political force and significance of the hibik poems.